PENDIDIKAN POLITIK DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Siti Rahmah; Iskandar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
Islam is a perfect religion that not only regulates ritualistic relationships between humans and their creators, but Islam is a comprehensive religion that regulates all aspects of human life both spiritually and physically, as well as regulates human affairs in social life and lays down the principles of the nation and state. State, including matters related to politics, power and government, political education, in political Islam known as siyasa which studies matters concerning matters concerning the affairs of the people and the state with all forms of law, regulation, and policies made by the holder of power. The Qur'an also uses the term Sulthan, "Physical ability to exercise influence and or coercion on other people or society" Mulk, "Power as an object of right (ownership)", and bukm "Organizing order in human life. What is more discussed is related to the principles of leadership where humans are the main subject and at the same time the object in politics. These principles are deliberation, trustworthiness, fair dealing, leadership is responsibility, leaders must not deceive their people, leaders do not do wrong to their people, leaders must pay attention to the condition of the Islamic Ummah (welfare), leaders must act fairly in governing, leaders love their people and their people love him, positions because they are trusted are mandated not requested. This research is a research library (library research).